2020
DOI: 10.1142/s0129167x20500251
|View full text |Cite
|
Sign up to set email alerts
|

A counter-example by Yagita

Abstract: According to a 2018 preprint by Nobuaki Yagita, the conjecture on a relationship between [Formula: see text]- and Chow theories for a generically twisted flag variety of a split semisimple algebraic group [Formula: see text], due to the author, fails for [Formula: see text] the spinor group [Formula: see text]. Yagita’s tools include a Brown–Peterson version of algebraic cobordism, ordinary and connective Morava [Formula: see text]-theories, as well as Grothendieck motives related to various cohomology theorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…In this section we shall collect some basic results on the Chow and the Grothendieck rings of maximal orthogonal grassmannians. For details and the general theory we refer the reader to [1], [2] and [9].…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section we shall collect some basic results on the Chow and the Grothendieck rings of maximal orthogonal grassmannians. For details and the general theory we refer the reader to [1], [2] and [9].…”
Section: Preliminariesmentioning
confidence: 99%
“…Recently, Yagita showed that G = Spin(17) provides a counter-example on the conjecture by Karpenko [10]. Later, Karpenko extended Yagita's counter-example to base fields of arbitrary characteristic [2]. However, as mentioned in [2, §1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the counter-example of [10] (see also [4]) provides by Theorem 3.1 a generic flag variety X (given by the spinor group Spin(17)) with non-trivial torsion in CK(X).…”
Section: Applications To Flag Varietiesmentioning
confidence: 99%
“…where CH(X) is the Chow ring, K(X) is the Grothendieck ring of X, and ChowK(X) is the ring associated with the Chow filtration (i.e., the filtration by codimension of supports of coherent sheaves) on K(X). Being recently disproved for G = Spin(17) by Yagita in [10] (see also [4]), Conjecture 1.1 has been confirmed for many other G. (For instance, the 2-local version for G of type E 7 is proved in the very [4].) An overview of some positive cases is given in [5].…”
mentioning
confidence: 98%